Media literacy in the system of higher education - Zaitseva, Natalia; Зайцева, Наталя Володимирівна; Зайцева, Наталья Владимировна (My University, 2017)
The article is devoted to the problem of media and informative literacy forming. The key points in the curriculum development process are represented. The importance of command of foreign languages for media literacy forming is stressed.
Keywords: media literacy; media-saturated environment; media landscape; command of foreign languages